Cross-Racial Supervision: Critical Issues in the Supervisory Relationship - Schroeder, Meadow; Andrews, Jac J. W.; Hindes, Yvonne L. (Canadian Journal of Counselling and Psychotherapy, 2009)
This paper reviews issues and findings from 13 research studies relative to cross-racial supervision. The research in this area indicates that a strong working alliance between the supervisor and student is more likely to happen when supervisors are culturally responsive and competent. However, in order to better appreciate the nature and scope of cross-racial supervision, future research needs to increase sample sizes and include the perspective of supervisors and students within the studies. Moreover, researchers should provide greater attention to the development of instruments they utilize in their studies to ensure reliability and validity of these measures.